(untitled) (Comprehensive Journal of Science, 2025)
This research addresses the importance of the role played by public relations activities in supporting and promoting a culture of dialogue and national reconciliation within societies that have experienced conflicts or political, social, or sectarian divisions. The study focuses on how public relations tools can be employee to build trust, reduce tension, and create an environment conducive to achieving sustainable reconciliation. It also examines the communicative methods used by public relations to spread a culture of understanding and tolerance among different components of society. The research, in its theoretical framework, explores the concept of public relations, and reviews the notions of national reconciliation and dialogue as two fundamental pillars for the stability of societies, highlighting the close interconnection between these three concepts and their complementary role in rebuilding the social fabric. The study used the descriptive analytical approach, and reached a set of results represented in the results showing the existence of a statistically significant linear relationship between the frequency of public relations activities and the level of promoting the culture of dialogue and reconciliation, as public relations activities explained about (26%) of the variance, with a medium effect (Beta = 0.509), The quality of messages has an impact on promoting a culture of dialogue and reconciliation, transparency in media practices has a strong positive impact on promoting a culture of dialogue and reconciliation, and trust-building efforts have a strong impact on promoting a culture of dialogue and reconciliation.